Experimental analysis of 13CO2 infrared stimulated: Low-Temperature Physics and Chemistry in Cryomatrice - Chabbi, H.; 1, P. R. Dahoo; 2, H. Dubost; Gauthier-Roy, B.; Vasserot, A.-M.; Abouaf-Marguin, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Vibrational stimulated emissions of CO2 trapped in low temperature argon matrices have been found experimentally not only in the 16 mm region (n2 manifold) but also at 10 mm (n3 - n1 transition) in the double trapping site of concentrated samples. A detailed experimental description of these emissions is reported, including spectral analysis, time-resolved studies, laser energy dependence, and concentration and temperature effects. The characteristics of the emissions are discussed, giving some insight into the nonradiative intramolecular V√V transfers from the laser excited level n3=1 towards the n2 manifold, and inside this manifold.